Sleep characteristics and inflammatory biomarkers among midlife women. Issue 5 (30th March 2018) - Nowakowski, Sara; Matthews, Karen A; von Känel, Roland; Hall, Martica H; Thurston, Rebecca C
Abstract: Study Objectives: Research suggests that sleep disturbances are associated with elevated levels of inflammation. Some evidence indicates that women may be particularly vulnerable; increased levels of inflammatory biomarkers with sleep disturbances are primarily observed among women. Midlife, which encompasses the menopause transition, is typically reported as a time of poor sleep. We tested whether poorer objectively measured sleep characteristics were related to a poorer inflammatory profile in midlife women. Methods: Two hundred ninety-five peri- and postmenopausal women aged 40–60 completed 3 days of wrist actigraphy, physiologic hot flash monitoring, questionnaires (e.g. Berlin sleep apnea risk questionnaire], and a blood draw for the assessment of inflammatory markers, including C-reactive protein (CRP), interleukin-6 (IL-6), and von Willebrand factor (VWF) antigen. Associations of objective (actigraphy) sleep with inflammatory markers were tested in regression models. Sleep efficiency was inverse log transformed. Covariates included age, race/ethnicity, education, body mass index, sleep apnea risk, homeostatic model assessment (a measure of insulin resistance), systolic blood pressure, low-density lipoprotein cholesterol, and physical activity. Results: In separate models controlling for age, race/ethnicity, and education, lower sleep efficiency was associated with higher IL-6 [ b ( SE ) = .02 (.10), p = .003] and VWF [ b (SE) = .02 (.08), p = .002]. More minutes awake after sleep onset was associated with higher VWF [ b ( SE ) = .12 (.06), p = .01]. Findings persisted in multivariable models. Conclusions: Lower sleep efficiency and more minutes awake after sleep onset were independently associated with higher circulating levels of VWF. Lower sleep efficiency was associated with higher circulating levels of IL-6. These findings suggest that sleep disturbances are associated with greater circulating inflammation in midlife women.